Bobwhite Quail and Changing Land Use - William D. Klimstra (National Quail Symposium Proceedings, 2017)
(Invited Paper) The downward trend of bobwhite quail (Colinus virginianus) numbers nationally is well established. Generally, this reflects deterioration and widespread loss of suitable habitat resulting from changes in land use. Since the 1940s research on the quail seems to have dwindled with few indications of on-going studies. There is much emphasis on setting aside areas as wilderness and natural areas and creating special funds, but these activities cannot accommodate the special needs of quail except in a general way. The intense emphasis on the economics of agriculture, use of chemicals in farming, and the activities of government and agricultural colleges have all but eliminated wildlife and diversity in many rural settings. Seemingly, a plausible course of action includes best land-use practices in concert with special programs of habitat development and preservation, an intensive effort to develop public awareness and support, the establishment of continuing long-term studies in connection with research-demonstration, a re-emphasis on well-trained field biologists with specialty in bobwhite ecology, a greater quail habitat management emphasis on public-controlled lands, a vastly improved and effective cooperation by various state and federal agencies, and carefully-planned and regulated land use for major soil types and/or ecosystems.